Synthesis, characterization, antimicrobial, analgesic and CNS studies of Schiff base cu(II) complex derived from 4-choro-o-phenylene Diamine - Deivanayagam, Piramanayagam; Bhoopathy, Parasuraman; Thanikaikarasan, Sethuramachandran (International Journal of Advanced Chemistry, 2014)
Schiff base ligand and its Cu (II) Complex had been synthesized by the condensation reaction of 4-chloro-o-phenylene diamine and 2-hydroxy acetophenone. The Structure and spectral properties of ligand and complex were confirmed by UV, FT-IR and 1H NMR Spectroscopy. The spectral properties showed that it was a square planar geomentry with a tetradentate ligand. The Schiff base Cu (II) Complex was subjected to antimicrobial studies. In this paper I have taken to discuss these three bactericidal organisms such as Bacillus subtilis, Streptococcus viridians and Staphylococcus epidermidis on the test compounds. Schiff base Copper (II) complex were screened by employing the Disc Diffusion method. A concentration gradient (5, 10, 20 and 30mg/ml) of each compound was put into study. From the study, it was observed that it showed a maximum zone of inhibition. The Schiff base complex were subjected to analgesic studies and it showed a significant increase in analgesic activity when compared with normal saline. The Schiff base complex was subjected to CNS studies and it showed a depressant activity when compared with standard drug chlorpromazine. Keywords: Schiff Base, 4-Chloro-O-Phenylene Diamine, Electronic Spectroscopy, Petri Plates and CNS.